Acute Hepatitis C Virus Infections in Spouses: The Utility of a Genetic Analysis of the Hepatitis C Virus Hypervariable Region Sequence for Identifying the Infectious Source - Okano, Hiroshi; Murakami, Masaru; Asakawa, Hiroki; Nose, Kenji; Tsuruga, Satomi; Tochio, Tomomasa; Kumazawa, Hiroaki; Sakuno, Takashi; Isono, Yoshiaki; Tanaka, Hiroki; Mats, Shimpei (Archives of Clinical and Medical Case Reports, 2021)
A married couple who developed hepatitis was referred to our hospital. The husband was diagnosed with acute hepatitis C virus (HCV) infection based on HCV RNA positivity and seroconversion to HCV antibody. The wife was also diagnosed with HCV-related hepatitis; however, she could not be confirmed to have acute hepatitis due to the lack of information on her HCV negativity just before this event. The HCV strains recovered from the couple were genotype 2b and shared 100% identities within the 5’-untranslated region-core region sequence (655 nucleotides/nt) and non-structural (NS)5B region sequence (502 nt). The amplified hypervariable region 1 (HVR-1) sequence indicated that all 10 clones from the wife shared 100% identity and were identical to 3 of 10 heterogeneous clones (separable into 4 groups) from the husband. The husband had a history of intravenous drug use. These results suggested that one of four quasispecies 2b HCV strains was transmitted from the husband to the wife, with the husband being the infectious source for acute HCV infection in the wife, most likely via sexual intercourse. A sequence analysis of the HCV genomes and the further comparison of the HVR-1 amino acid sequence variability may be useful for defining the infectious source of HCV, especially in couples or cluster cases.